The vaccination debate in the "post-truth" era: social media as sites of multi-layered reflexivity - Numerato, Dino; Vochocová, Lenka; Štětka, Václav; Macková, Alena (Sociology of health & illness, 2019)
This paper analyses the contemporary public debate about vaccination, and medical knowledge more broadly, in the context of social media. The study is focused on the massive online debate prompted by the Facebook status of the digital celebrity Mark Zuckerberg, who posted a picture of his two-month-old daughter, accompanied by a comment: 'Doctor's visit - time for vaccines!' Carrying out a qualitative analysis on a sample of 650 comments and replies, selected through systematic random sampling from an initial pool of over 10,000 user contributions, and utilising open and axial coding, we empirically inform the theoretical discussion around the concept of the reflexive patient and introduce the notion of multi-layered reflexivity. We argue that the reflexive debate surrounding this primarily medical problem is influenced by both biomedical and social scientific knowledge. Lay actors therefore discuss not only vaccination, but also its political and economic aspects as well as the post-truth information context of the debate. We stress that the reflexivity of social actors related to the post-truth era re-enters and influences the debate more than ever. Furthermore, we suggest that the interconnection of different layers of reflexivity can either reinforce certainty or deepen the ambiguity and uncertainty of reflexive agents.
Keywords: vaccine; post-truth; Social Media; reflexivity; Vaccination; sociální média; zdraví - znalosti, postoje, praxe; Humans; vakcinace; Facebook; social media; conspiracy theory; lidé; Health Knowledge, Attitudes, Practice